1972
DOI: 10.1116/1.1316623
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Transport Properties of Vacuum Evaporated Selenium Films

Abstract: The transport properties of vacuum evaporated films of “pure” selenium and selenium doped with small quantities of Cl (0–40 ppm) and As (∼12at.%) have been examined using a time-resolved drift technique. Addition of Cl alone acts as an electron trap, and addition of As alone acts as a hole trap while greatly increasing the electron free-carrier lifetime. When used in combination, controlled addition of these two impurities can be used to produce hole ranges greater than 7.5×10−6 cm2/V and electron ranges great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The measurements were on vacuum deposited films and in all cases, during evaporation, the substrates (usually oxidized Al plates) were heated to around 55-60°C, which is above the glass transition temperature, which is known to result in good hole transport [45]. The preparation of a-Se based films has been well described in the literature [32,[46][47][48], including in this journal [8,49]. In TOF experiments, a semitransparent top electrode is deposited onto the surface of a-Se, which is often gold.…”
Section: Introduction and Perspectivesmentioning
confidence: 99%
“…The measurements were on vacuum deposited films and in all cases, during evaporation, the substrates (usually oxidized Al plates) were heated to around 55-60°C, which is above the glass transition temperature, which is known to result in good hole transport [45]. The preparation of a-Se based films has been well described in the literature [32,[46][47][48], including in this journal [8,49]. In TOF experiments, a semitransparent top electrode is deposited onto the surface of a-Se, which is often gold.…”
Section: Introduction and Perspectivesmentioning
confidence: 99%
“…It was subsequently observed that this unfavourable effect could be countered through the addition of Cl in the 10-20 ppm range [5,6].…”
mentioning
confidence: 95%
“…Table I lists the samples we have studied in this work, which included pure a-Se, sample A. B1 and B2 have the same composition (a-Se:0.2%As) but the material is from two different batches; batch to batch variation of electronic properties is well known for a-Se. 30 Samples C1 and C2 represent stabilized a-Se that has been doped with Cl and CaCl 2 in the ppm range.…”
Section: Methodsmentioning
confidence: 99%